Coupled Fixed Point Theorems for Weak Contraction Mappings under F-Invariant Set - Wutiphol Sintunavarat; Yeol Je Cho; Poom Kumam (Abstract and Applied Analysis)
We extend the recent results of the coupled fixed point theorems of Cho et al. (2012) by weakening the concept of the mixed monotone property. We also give some examples of a nonlinear contraction mapping, which is not applied to the existence of the coupled fixed point by the results of Cho et al. but can be applied to our results. The main results extend and unify the results of Cho et al. and many results of the coupled fixed point theorems.